Upaya Kepala Sekolah dalam Meningkatkan Mutu Pendidikan di Kabupaten Pesisir Selatan - Bashori, Bashori; Delanda, Puja Dwi; Zulmuqim, Zulmuqim; Usdarisman, Usdarisman (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2021)
This study aims to analyze the principal's efforts in improving the quality of educational institutions. This study uses a descriptive method, with interview data collection techniques and documentation. Data analysis techniques in research are data collection, data reduction, data presentation and conclusions. The results of this study indicate that the principal has made efforts to improve the quality of education through management concepts, namely; (1) Program planning; (2) Organizing activities; (3) Implementation of activities; and (4) Control of activities.